2017
DOI: 10.1523/jneurosci.3689-16.2017
|View full text |Cite
|
Sign up to set email alerts
|

Segregation of Visual Response Properties in the Mouse Superior Colliculus and Their Modulation during Locomotion

Abstract: The superior colliculus (SC) receives direct input from the retina and integrates it with information about sound, touch, and state of the animal that is relayed from other parts of the brain to initiate specific behavioral outcomes. The superficial SC layers (sSC) contain cells that respond to visual stimuli, whereas the deep SC layers (dSC) contain cells that also respond to auditory and somatosensory stimuli. Here, we used a large-scale silicon probe recording system to examine the visual response propertie… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

14
104
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 81 publications
(119 citation statements)
references
References 63 publications
14
104
1
Order By: Relevance
“…Where there is overlap, our measurements in awake animals are also consistent with a recent study by Ito et al . () reporting similar distributions of spatial frequency preference, linearity of spatial summation, and prevalence of orientation and direction selectivity.…”
Section: Discussionmentioning
confidence: 83%
See 3 more Smart Citations
“…Where there is overlap, our measurements in awake animals are also consistent with a recent study by Ito et al . () reporting similar distributions of spatial frequency preference, linearity of spatial summation, and prevalence of orientation and direction selectivity.…”
Section: Discussionmentioning
confidence: 83%
“…; Ito et al . ; Shi et al . ), consistent with the projection of direction selective retinal ganglion cells (Kim et al .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…; Gale & Murphy, ; Ito et al . ), they found that in both conditions most neurons in the SC respond to both white and black spots on a grey background, and that their On and Off subfields were overlapping. Interestingly, they found differences in the response of SC neurons to drifting gratings.…”
mentioning
confidence: 92%